Fuel options for the future: a comparative overview of properties and prospects (Transport systems and technologies, 2023)
As the maritime industry seeks to reduce its impact on the environment, the search for alternative fuel options is becoming increasingly important. Various fuel options are being studied, including biofuels, hydrogen, and ammonia, which are considered to be more environmentally friendly than traditional fuels extracted from the Earth's depths. The choice of fuel depends on various factors, including the size, speed, and distance of the ship, as well as the availability and cost of fuel. In the future, a combination of different fuel options may be necessary to achieve emission reduction goals. This article compares different alternative fuel types for ships, including low-sulfur fuel, LNG, electricity, methanol, hydrogen, and ammonia. Research shows that low-sulfur fuel is expensive but still cheaper than LNG, and the process of transitioning a ship to this type of fuel is relatively simple. LNG is the most expensive type of fuel and requires a complete overhaul of the ship's fuel system, which reduces its profitability. The article provides a table comparing the properties of different fuel types and concludes that methanol is likely to be the most promising alternative fuel in the near future.
Keywords: safe energy policy, ecology, environmental protection, pollution of atmosphere, low sulphur.